(untitled) (Fiep Bulletin - online, 2014)
The acquired motor ability in the first years of infancy will be perfected later in the adult phase. The development of the motor coordination and the balance only occurs through child day by day, this means that the practice of regular sporting activities is necessary. Studies performed in genetics area indicate a relation of dermatoglyphic indexes with tendency for coordinate qualities of the organism and affirm that use of the previous knowledge of the capacities and genetic trends, allied to the phenotypic contribution, would give aid, either in talent determination or in its global development. The objective of the present study is centered in the comparison of the behavior of static balance, dynamic balance and motor coordination of children from 5 to 7 years practicing and not practicing swimming. The groups had been compared in its complete form and later divided in accordance with the genotype. For dermatoglyphics impressions analysis, Cummins & Midlo (1961) protocol was used and for evaluation of the balance condition, Lefèvre (1972) protocol was used. The characteristic of this study is a descriptive research whose delineation is comparative. The experimental groups, masculine and feminine, had presented significant differences, before and after testing, in the results of motor coordination testing. In static balance and dynamic balance tests, they presented a 100% utilization after-test. On the other hand, in experimental groups divided by genotype, only experimental groups, masculine and feminine, of lesser genetic predisposition to the coordination had presented significant differences in its results. With the work performed through swimming, we observed satisfactory results for motor development of these children having as reference their genotypical characteristics.